Designing a Functioning Community Forest Association: A Case of Muileshi, Kakamega County, Kenya (Asian Journal of Applied Sciences, 2016)
Participatory Forest Management was introduced into law with the passing of the Kenya Forest Act of 2005, which provides a legal basis for communities in Kenya, to participate in forest management.Â  In Kenya Participatory forest management entails the involvement of the forest adjacent community members through formation of Community Forest Associations, which participates in the management of the forest with the Kenya Forest Service (KFS) and other stakeholders. This paper examines the design and functioning of Muileshi community forest Association in Kakamega Kenya to answer a key question in current participatory forest management literature on how one can design a functioning community forest association that can conserve the forest resources as well as provide sustainable livelihoods to the poor forest dependent communities. The study utilized documents and a focus group discussion with Muileshi community forest association to answer this question. All the data collected was qualitatively analyzed by putting the key themes together from both the documents and focus group discussion and using them to answer the study objective. It is conclude in the study that a well designed community forest association can contribute significantly to the conservation a community based forest as well as deliver livelihoods to the communities adjacent to the forests that depend on them for their livelihoods.Â  It is recommended that there is need to strengthen the community forest association arrangements to enable them operate efficiently. This paper intends to answer a key question in current literature on how one can design a function CFA that can conserve forests and deliver sustainable livelihoods to communities depended on those forests?Â